Cultural and philosophical analysis of theatrical art in Kazakhstan - Boranbayev, A.A. (Karaganda University named after academician E.A.Buketov, 2023)
This article considers the ways of professional development of kazakh directing in the era of globalization, having studied the artistic horizons of modern theatrical art from a new point of view. The directions of continuity of the theatre sphere, which is an artistic and aesthetic phenomenon in the culture of our state, from ancient times to the present day are considered. The national character of the country's theatrical directing is considered the trends of its development in the context of cultural and philosophical contexts. Theatrical art is a spiritual, social, artistic and aesthetic beginning for the nation from analysis of the current trends in the development of theatrical directing in Kazakhstan, determining its existence and essence. The role of the theatre industry is determined in a globalizing society in the preservation and development of the image and image of the nation. Scientific and theoretical analysis of the creative heritage of outstanding national directors will be carried out. The purpose of this study is to determine the role of theatrical art for the socio – cultural space of modern Kazakhstan, to determine the role of theatrical amateurs in the formation of modern kazakh culture, to identify interaction with other elements of the socio-cultural system.
Қазақстандағы театр өнерін мәдени-философиялық талдау
Культурно-философский анализ театрального искусства Казахстана
Keywords: theatre; directing; philosophy; culture; value; virtue; prosperity; globalization; Kazakhstan